Burns in Baghdad from 2003 to 2014: Results of a randomized household cluster survey. Issue 1 (February 2016) - Stewart, Barclay T.; Lafta, Riyadh; Esa Al Shatari, Sahar A.; Cherewick, Megan; Burnham, Gilbert; Hagopian, Amy; Galway, Lindsay P.; Kushner, Adam L.
Highlights: Burns increased post-invasion from 39 per 100, 000 persons in 2003 to 117 in 2013. Unlike peacetime epidemiology, burns were more common in men and older adults. Death (16%), disability (40%), and food insecurity (50%) were common after burns. Abstract: Purpose: Civilians living amid conflict are at high-risk of burns. However, the epidemiology of burns among this vulnerable group is poorly understood, yet vital for health policy and relief planning. To address this gap, we aimed to determine the death and disability, healthcare needs and household financial consequences of burns in post-invasion Baghdad. Methods: A two-stage, cluster randomized, community-based household survey was performed in May 2014 to determine the civilian burden of injury from 2003 to 2014 in Baghdad. In addition to questions about cause of household member death, households were interviewed regarding burn specifics, healthcare required, disability, relationship to conflict and resultant financial hardship. Results: Nine-hundred households, totaling 5148 individuals, were interviewed. There were 55 burns, which were 10% of all injuries reported. There were an estimated 2340 serious burns (39 per 100, 000 persons) in Baghdad in 2003. The frequency of serious burns generally increased post-invasion to 8780 burns in 2013 (117 per 100, 000 persons). Eight burns (15%) were the direct result of conflict. Individuals aged over 45 years had more than twice the odds of burn than children aged less than 13 years (aOR 2.42; 95%CI 1.08–5.44). Nineteen burns (35%) involved ≥20% body surface area. Death (16% of burns), disability (40%), household financial hardship (48%) and food insecurity (50%) were common after burn. Conclusion: Civilian burn in Baghdad is epidemic, increasing in frequency and associated with household financial hardship. Challenges of healthcare provision during prolonged conflict were evidenced by a high mortality rate and likelihood of disability after burn. Ongoing conflict will directly and indirectly generates more burns, which mandates planning for burn prevention and care within local capacity development initiatives, as well as humanitarian assistance.